1992
DOI: 10.1093/clinids/14.6.1251
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Treatment of Orthopedic Implant-related Infections with Rifampin Combinations

Abstract: The purpose of this prospective clinical study is to evaluate the role of combination chemotherapy with rifampin in the treatment of orthopedic device-related infections in which the implant could not be removed. Eleven patients with orthopedic implant-related infections due to staphylococci or streptococci were treated with the implant in situ. Each antimicrobial regimen included rifampin in combination with a 19-lactam antibiotic or ciprofloxacin. The median duration of treatment with rifampin was 86 days (r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
145
1
6

Year Published

1998
1998
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 236 publications
(160 citation statements)
references
References 9 publications
8
145
1
6
Order By: Relevance
“…Rifampicin is a potent antibiotic that is especially effective against Staphylococcus, which sometimes show resistance to beta-lactam antibiotics (Henry et al, 1987;Dworkin et al, 1990;O'Reilly et al, 1992;Littlewood-Evans et al, 1997;Rissing, 1997;Costerton et al, 1999). Furthermore, rifampicin has been shown to be an effective agent for treating bacteria in biofilms (Widmer et al, 1992), which Costerton et al (1999) reported to be important in the pathogenesis of bone and joint infection. Therefore, rifampicin has been recommended in the treatment of prosthesis infections (Rissing, 1997).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rifampicin is a potent antibiotic that is especially effective against Staphylococcus, which sometimes show resistance to beta-lactam antibiotics (Henry et al, 1987;Dworkin et al, 1990;O'Reilly et al, 1992;Littlewood-Evans et al, 1997;Rissing, 1997;Costerton et al, 1999). Furthermore, rifampicin has been shown to be an effective agent for treating bacteria in biofilms (Widmer et al, 1992), which Costerton et al (1999) reported to be important in the pathogenesis of bone and joint infection. Therefore, rifampicin has been recommended in the treatment of prosthesis infections (Rissing, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies shown that after oral administration of rifampicin, the rifampicin concentration in bone and in the joint tuberculosis focus was lower than the effective bactericidal concentration (Roth, 1984;Widmer et al, 1992;Mahajan et al, 1997;Zimmerli et al, 1998;Isefuku et al, 2001). Therefore, the topical application of rifampicin on tuberculosis foci has been considered as an approach worth investigating.…”
Section: Introductionmentioning
confidence: 99%
“…The duration of symptoms is important, since several studies have shown a high success rate (82-100%) with debridement and retention, if the duration is 3 weeks (Burger et al 1991, Widmer et al 1992, Zimmerli et al 1998, Tattevin et al 1999, Meehan et al 2003, Barberan 2006, Laffer et al 2006. The time to diagnosis of infection, described by Choong et al (2007) ranged from 5 to 105 days.…”
mentioning
confidence: 99%
“…When infections occur within 4 weeks of implantation, the implant can be left in place with a high probability of implant survival of between 80% and 100%, whereas late infections generally require prosthesis revision to control the infection [7,22,44,45].…”
Section: Introductionmentioning
confidence: 99%